In vitro Antimycobacterial, Apoptosis-Inducing Potential, and Immunomodulatory Activity of Some Rubiaceae Species - Aro, Abimbola O.; Dzoyem, Jean Paul; Goddard, Amelia; Fonteh, Pascaline; Kayoka-Kabongo, Prudence N.; McGaw, Lyndy J. (Frontiers in Pharmacology, 2019)
Tuberculosis (TB), a disease caused by microorganisms of the Mycobacterium tuberculosis complex, infects almost one-third of the world’s population. The TB epidemic has been further exacerbated by the emergence of multi, extensively, and totally-drug-resistant (MDR, XDR, and TDRTB) strains. An effective immune response plays a crucial role in determining the establishment of TB infection. Therefore, the modulation of the immune system has been considered as a vital approach for the treatment or control of various immune-related diseases such as TB. In this study, the antimycobacterial, immunomodulatory, and apoptosis-inducing effects of six Rubiaceae species were evaluated. A twofold serial dilution method was used to determine the minimum inhibitory concentration values of the plant extracts. The effect of the extracts on the activity of 15-lipoxygenase was investigated. The levels of six different cytokines, IL-2, IL-4, IL-5, IL-10, IFN-γ, and TNF-α, were measured in LPS-activated U937 cell line while the apoptosis-inducing effect of the extracts was evaluated using an annexin V/PI assay using a flow cytometer. The results obtained revealed that all the six extracts tested had antimycobacterial activity against M. tuberculosis H37Rv, M. tuberculosis ATCC 25177, and Mycobacterium bovis ATCC 27299 strains, with MIC values ranging from 39 to 312 μg/mL. The extracts of Cremaspora triflora and Cephalanthus natalensis were the most active against M. tuberculosis (MIC = 39 μg/mL), followed by Pavetta lanceolata and Psychotria zombamontana against M. bovis (MIC = 78 μg/mL). The extracts of P. zombamontana and Psychotria capensis had remarkable IC50 values of 4.32 and 5.8 μg/mL, respectively, better than that of quercetin. The selected extracts promoted Th1/Th2 balances in an in vitro model at the tested concentration which may suggest the therapeutic value of the plant in diseases where inflammation is a significant factor such as TB. The addition of the crude extracts of C. triflora, P. capensis, and P. zombamontana at the tested concentrations to the cell culture medium induced apoptosis in a time- and dose-dependent manner. This interesting preliminary result generated from this study encourages further investigations of these extracts owing to the LOX-inhibitory effect, immunomodulatory, and apoptotic-inducing properties in addition to their antimycobacterial properties.